COMPARISION OF REFLECTIVITY INVERSION USING A BASIS PURSUIT INVERSION METHOD WITH RICKER WAVELET AND WAVEZ ON A THIN BED AT SASWI FIELD - Ihsan Rezandy (NIM : 12313017, Muhammad
Seismic inversion has been long used for reservoir characterization. There are many methods in seismic inversion, one of them namely basis pursuit inversion (BPI). BPI will provide a reflectivity model which is basically similar to the original reflectivity model. The reflectivity model can be achieved by finding the solution in dictionary matrix, which consist of odd-pair and even-pair of reflectivity coefficients which are arranged in wedge model. Dictionary matrix then used to find the solution of an algorithm to achieved the result of Basis Pursuit Inversion. Due to its over-completeness of dictionary, BPI can resolve thin layer reservoir. However, BPI as inversion method depends on the predicted wavelet, the same as other inversion methods. Miss-predicted wavelet, both of frequency and phase, can produce different result of inversion . In this research, BPI is applied to study the strengths and weaknesses of BPI. Some experiments are analyzed to get the tolerances of miss-prediction in BPI method. Moreover, it is given other solution to solve the weakness of the method. In this research, writer used 2 wavelets, which is ricker wavelet and wavez wavelet. The result of this research is basically to compare the 2 wavelets (ricker and wavez) in giving the best reflectivity model which is similar to the original reflectivity and to find out the threshold of wavez wavelet in giving a solution